Advanced Thermodynamics. - Tabatabaian, Mehrzad (Mercury Learning & Information, 2017)
Designed for the senior/graduate level course in thermodynamics or for use as a reference for practicing engineers, this book includes the theoretical underpinnings and derivations necessary for advanced study as well as numerous applications from industry. A companion CD-ROM with figures and MATLAB files is included. Modern software tools, such as EXCEL and MATLAB, are used to solve mathematically challenging problems. Starting with the First and Second Laws of Thermodynamics, the book shows how the principles of thermodynamics apply to engine and power plant design. Applications include combustion of traditional fossil-fuels, pollutants and their effects, and alternative energy technologies-- including fuel cells, solar power, and wind power. Features:* Includes a companion CD-ROM with files of images, figures, property data tables, and MATLAB codes * Uses modern applications, e.g., alternative energy technologies to reinforce concepts* Provides classical theoretical underpinnings and derivations* Instructor's resources available upon adoption.